Digitalization of the HR management system in international business - Kobielieva, T. O.; Kopytsia, A. O. (Харківський національний університет міського господарства імені О. М. Бекетова, 2025)
Digitalization of the HR system is a necessity for international business, as it helps to increase work efficiency, minimize risks and allows you to adapt to the dynamic conditions of the global market. The use of modern HRM solutions helps companies attract and retain talent, creating favorable conditions for their productive work. Success in international business depends on how quickly a company integrates digital technologies into its HR strategy.
Діджиталізація системи управління персоналом у міжнародному бізнесі
Keywords: HR; digitalization; business processes; efficiency; international activities